Strategies of Overcoming Challenges in Travel Guides Translation (a Corpus-Based Study) - Irina Mkhitaryan; Tsoghik Grigoryan (Translation Studies: Theory and Practice, 2022)
The action research is a parallel corpus study that delves into the translation peculiarities of translated English travel guides and a few websites. The corpus is based on Newmark`s strategies which endorse the availability of effective analyses. The results of the findings have shown: (a) as a full expression of simplification, one of the translation universals, translated English tourism texts are more concise than their Armenian source texts through the omission of detailed information in listings and culture-specific information in the original ; (b) translated English tourism texts are more formal and detached in tone than that of Armenian original through the frequent adoption of nominalization; (c) translation strategies are of great avail to find out mistranslations and misinterpretations of the tourist texts. The very research instantiated intricacies between the translated English tourism texts and the source text in Armenian by highlighting the thematic and formal features of tourism discourse in translation, which may also become an essential pedagogic platform in translating tourism texts from Armenian into English.